(untitled) (Journal of Information and Computing Science, 2025)
In this article a new preconditioner from class of (I+S)-type based on the Modified Accelerated Overrelaxation(MAOR) iterative method has been introduced and convergence properties of the proposed method have been analyzed and compared with the some other preconditioners. Moreover, comparisons between different splittings are derived. Numerical example is also given to illustrate our results.